Ideološka podstat vladavine prava - Spruk, Jure (Teorija in praksa, 2021)
The study of the ideological foundations of the rule of law acknowledges that this principle is not just a formalism. In addition, it acknowledges that the material view of these principles derives from foundational moral and political values which form part of constitutional documents and are also the values of a certain broader ideological framework that denotes the political scheme of a particular political community. Ideology is not defined as a negative burden on some political space, but is seen as a necessary prerequisite for the activity and effectiveness of the political. Determination of the form of government is a product of the political process and, in this sense, the rule of law has its own ideological foundation in classical liberalism, which historically emerges from the values of liberty and formal equality as values challenging feudalism and absolutism. The rule of law was created on the grounds of liberty and formal equality as an instrument of limiting the central government in the modern state, as encouraged by the whole political relationships balanced in favour of the liberal bourgeoisie in their political battle against feudal aristocracy.
Keywords: Ideologija; Ideology; ideološki temelji; Liberalism; Liberalizem; moderna država; Pravna država; Rule of law; vladavina prava